2016
DOI: 10.1002/ejic.201600408
|View full text |Cite
|
Sign up to set email alerts
|

Solids Go Bio: Inorganic Nanoparticles as Enzyme Mimics

Abstract: The cover image shows inorganic nanoparticles that mimic the catalytic activity of naturally occurring enzymes. The nanoparticles are more stable and cost-efficient, and their high surface area endows them with a large number of active sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Since the first evidence of ferromagnetic nanoparticles as peroxidase mimetics was reported in 2007 1 , various nanomaterials have been identified that possess intrinsic enzyme-like activities 2 6 . These materials catalyze enzymatic reactions and follow similar enzymatic kinetics and mechanisms of natural enzymes under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first evidence of ferromagnetic nanoparticles as peroxidase mimetics was reported in 2007 1 , various nanomaterials have been identified that possess intrinsic enzyme-like activities 2 6 . These materials catalyze enzymatic reactions and follow similar enzymatic kinetics and mechanisms of natural enzymes under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial species shows selectivity for particular nanoparticles. Silver nanoparticles shows antibacterial activity efficiently than copper nanoparticles aganist E. coli and S. aureus, while B. subtilis shows more susceptibility to copper nanoparticles than silver nanoparticles [34]. Nanoparticles of titanium dioxide shows greater antibacterial activity against E. coli than S. typhimurium.…”
Section: Introductionmentioning
confidence: 95%
“…[27] Other excellent in-depth reviews on the nanozyme concept and broad applications are available elsewhere. [6, 14, 28, 29] Here, we focus on emerging biomedical applications of catalytic nanomaterials, and their progress towards clinical use based on recent findings using in vivo models.…”
Section: Intrinsic Enzyme-like Properties Of Nanomaterialsmentioning
confidence: 99%